Development of Thai Pandan Coconut Pudding Recipe by Adding Bamboo Leaf Juice - อ่อนน้อมพันธุ์ ผู้ช่วยศาสตราจารย์เอกพล; ภาสุรกุล ปวิตรา; ประเคนแสง นิลุบล; วิเทศ จารุณี; วิเทศ จารุณี; บุญญสิริสกุล ไพรินทร์ (Journal of Food Health and Bioenvironmental Science, 2017)
The objective of this research were: to develop the Thai pandan coconut pudding recipe and examine the chemical, sensory, and nutritional qualities of the pudding. The three original recipes of Thai pandan coconut pudding were tested to select the best recipe that was accepted by the testers, and the accepted recipe was tested to find the appropriate amount of bamboo juice to add to the Thai pandan coconut pudding. The proportion between pandan juice and bamboo juice were 50:50, 25:75 and 0:100, respectively, and were evaluated for the following criteria: appearance, color, odor, flavor, texture, and overall preference. The data was collected from a group of 100 testers who were lecturers and students from the Home Economics Program at Suan Dusit School of Culinary Arts. The results of evaluation were measured using a 9-point hedonic scale. The research has shown that the proportion of 25:75 was the most accepted proportion with the overall satisfaction at 7.29a ± 0.828. The nutritional value of 100 grams of Thai pandan coconut pudding with bamboo juice added at the proportion of 25:75 contains 142 Calories, protein 1.32 grams, carbohydrate 34.12 grams, fat 0.08 grams, dietary fiber 0.25 grams, beta carotene 22 µ g, moisture 64.33 grams and ash 0.15 grams. The cost of manufacturing is 0.72 Baht cheaper per serving compared to the original recipe. The results have shown that local vegetables such as bamboo leaf can be appropriate for Thai dessert. Bamboo juice has high nutritional value, low cost and acceptable flavour. The result from this research should be developed and applied for cooking Thai dessert in the schools, served at government offices, be use as alternative healthy Thai appetizer for every people.